(untitled) (Research, Society and Development, 2022)
Objective: The present study aims to review the literature on neonatal neurological disorders caused by the use of crack and cocaine during pregnancy. Methodology: This is an integrative literature review, with a qualitative and quantitative approach. Based on articles indexed in the Virtual Health Library databases, the Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library onLine and PUBmed data sources. Results: In the bibliographic survey, 11 articles were found in LILACS, 14 in the VHL and 81 in SCIELO, after applying the inclusion and exclusion criteria, 18 were selected that directly contributed to the construction of this study. Conclusion: It is concluded that the negative effects of the use of psychotropic drugs during pregnancy reflect the absence of prenatal care, as well as the lack of support and encouragement to abandon the addiction, since people who make chronic use of these drugs suffer from withdrawal syndromes caused by the lack of substances in the body of these individuals. Other related complications are: miscarriage, placental abruption, preterm labor, uterine rupture, cardiac dysrhythmias, liver rupture, cerebral ischemia, infarction and death.